Human Resources as Brand Ambassador: a Qualitative Approach to Building Customer Loyalty - Rostini; Razak, Annisa Zhalila; Muhammad, A Fadel; Sukiman; Hamsyah (PT. Maju Malaqbi Makkarana, 2025)
In an increasingly competitive business world, building customer loyalty does not solely depend on product quality but also on interactions that foster trust and emotional connection. This study explores the role of Human Resources (HR) as Brand Ambassadors in enhancing customer loyalty through a qualitative approach. The research method employed is a case study, utilizing in-depth interviews, participatory observation, and document analysis as data collection techniques.The findings indicate that internal brand ambassadors are more effective than celebrities or influencers as they have a deeper understanding of the product and company values. Direct interaction between internal brand ambassadors and customers creates a more authentic experience, strengthens trust, and enhances brand loyalty. Additionally, value alignment between employees and the company plays a crucial role in the success of this strategy. This study suggests that companies aiming to improve customer loyalty can optimize the role of HR as brand ambassadors. By fostering more personal and authentic interactions, internal brand ambassadors contribute to the development of long-term relationships between customers and brands